Журавль в небе: [повесть] / Т. Воробей - Воробей Таня (Мой первый роман, 2003)
6-8 кл. Экземпляры: (20190120) / Инвентарный номер: 30931 / Цена: 36.50 / Сис.шифр: Р2 / Авт.знак: В75 / ГРНТИ: 17 / ББК: 84(2Рос=Рус)6